PENGARUH PENGENDALIAN INTERNAL DAN AUDIT INTERNAL TERHADAP PENCEGAHAN FRAUD DENGAN ANTI-FRAUD AWARENESS SEBAGAI PEMODERASI PADA INDUSTRI PERBANKAN INDONESIA - Billa, Rahma Dhina Salsa; Indriani, Mirna (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2023)
This study aims to examine the effect of internal control and internal audit on fraud prevention, as well as investigate whether anti-fraud awareness can moderate the relationship between internal control and internal audit on fraud prevention in the Indonesian banking industry. This study used 138 respondents consisting of Indonesian banking employees. These respondents came from Indonesian commercial banks. The data collection used in this study is a questionnaire distributed using Google Forms to the respondents starting from July to August 2022. This study uses PLS-SEM (Partial Least Square Structural Equation Modeling) as a method of data analysis and uses WarpPLS software version 7.0 as a data processing tool. The findings of this study indicate that internal control and internal audit have a positive relationship to fraud prevention and the anti-fraud awareness variable is able to moderate the relationship between internal control and internal audit with fraud prevention. These findings are expected to be a perspective for Indonesian banks in preventing potential fraud in their organizations.